Supramolecular Immunotherapy of Cancer Based on the Self‐Assembling Peptide Design. Issue 2 (13th September 2020) - Chang, Rui; Yan, Xuehai
Abstract : Supramolecular peptide assemblies with specific motifs have the advantages of high immunogenicity, regulated immune response, and increased multiple functions in improving the performance of cancer immunotherapy, compared with molecular peptide immunotherapy. These peptide‐based assemblies with structural and functional versatility can serve as immunotherapeutic agents such as antigens, adjuvants, drug delivery carriers, or immunomodulators. This article reviews the effects of supramolecular peptide assemblies on cancer immunotherapy and highlights the unique role of supramolecular assembly strategies in regulating the immunotherapeutic performance. The mechanism of how the peptide supramolecular self‐assembly affects the performance of immunotherapy is critically emphasized. The summary of peptide supramolecular immunotherapy provides a reference for the precise design of adjustable and multifunctional immunotherapeutic agents, and shows that peptide self‐assembly has great application prospects in cancer immunotherapy. Abstract : Supramolecular peptide assemblies have the advantages of enhancing immunogenicity and stability, and act as antigens, adjuvants, carriers, or immunomodulators in tumor immunotherapy. In addition, supramolecular peptide assemblies have the ability to combine immunotherapy with chemotherapy and phototherapy to solve the problem of insufficient immunotherapy, thereby exerting a synergistic effect and enhancing antitumor effects.